Exercise health belief model mediates the relationship between physical activity and peer support among Chinese college students: A cross-sectional survey - Sheng, Jiazhi; Gong, Lamei; Zhou, Jian (Frontiers in Psychology, 2023)
This investigation will explore the influence of exercise health beliefs model (EHBM) and peer support (sup) on college students' physical activity (PA), and clarify the related mechanism. Participants and methods: Three hundred thirty-six healthy college students (age 19.4 ± 1.3 years, 166 males and 170 females) from a college in China, and who were evaluated by the sup scale, EHBM scale, and PA scale (short volume). Results: The results showed that male' exercise self-efficacy (eff-e) and PA were markedly higher than female college students. Sup was positively correlated with perceived benefits (ben), eff-e, perceived severity (sev), and cues to action (cues), and adversely associated with perceived objective barriers (oba), subjective barriers (sba). PA was positively correlated with ben and eff-e, and negatively correlated with oba and sba. Among the components of EHBM, only eff-e was suitable for constructing a structural equation model (SEM) with sup and PA. Based on analysis showed that the predictive effect of eff-e on PA was greater than sup, and eff-e played a critical intermediary role. It was worth noting that in the grouping model, the effect of male college students' eff-e on PA was 0.63, which was greater than that of female (0.48), and the fitting degree of sup from male college was better than that of female. Although the impact of sup on PA was less than that of eff-e, and the direct effect of sup was less than the indirect effect, the impact of sup on the PA of female college students was higher than that of male. Conclusions: This study revealed the impact of eff-e and sup on college students' PA, suggested that eff-e is the main path to promoting college students' PA, followed by sup. Sup could affect college students' PA not only through direct effects, but also indirect effects. This study also suggested that female college students' sup has a higher impact on PA than male. Therefore, this was a suggest that when formulating physical exercise courses in the future, it is necessary to give more sup to female college students to compensate for the insufficient of eff-e.